USE OF THE LINKEDIN APPLICATION ON BRAND AWARENESS AND CORPORATE IMAGE (LITERATURE REVIEW STUDY) - Sameer Seth (Dinasti International Journal of Digital Business Management, 2022)
The Literature Review article on the Use of the Linkedin Application on Brand Awareness and Corporate Image is a scientific article that aims to build a research hypothesis on the influence of inter-variables to be used in further research. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this study include: 1) the Linkedin application has an effect on brand awareness; 2) The LinkedIn application has an effect on corporate image; and 3) Brand awareness has an effect on corporate image.